Self-supported sulphurized TiO2 nanotube layers as positive electrodes for lithium microbatteries. (September 2019) - Salian, Girish D.; Krbal, Milos; Sopha, Hanna; Lebouin, Chrystelle; Coulet, Marie-Vanessa; Michalicka, Jan; Hromadko, Ludek; Tesfaye, Alexander T.; Macak, Jan M.; Djenizian, Thierry
Graphical abstract: Highlights: Synthesis of sulphurized TiO2 nanotubes has been achieved. Sulphurized TiO2 nanotubes is a good cathode material for Li microbatteries. The presence of sulphur improves the electrochemical properties. The stability of sulphurized TiO2 nanotubes electrodes is outstanding. A layer composed of lithium sulphides is responsible for the initial capacity fade. Abstract: We report the synthesis and characterization of self-supported sulphurized TiO2 nanotube layers as a cathode material for Li microbatteries. Sulphurized TiO2 nanotubes were obtained by annealing of self-supported TiO2 nanotubes in sulphur atmosphere. The morphology, structure, composition and thermal stability of the Ti x O y S z nanotube layers were studied by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy and thermogravimetric analysis. The electrochemical behaviors of the chemically modified nanotubes were investigated by cyclic voltammetry and chronopotentiometry techniques. This nanostructured electrode used as a cathode material showed high rate capabilities even at very fast kinetics. Remarkably, a high discharge capacity (340 μAh cm −2 ) has been retrieved after 100 cycles with 100% coulombic efficiency attesting the excellent stability of the electrode.